Thyroid dysfunction and Alzheimer's disease, a vicious circle - Li, Zhaoqing; Liu, Jia (Frontiers in Endocrinology, 2024)
Recently, research into the link between thyroid dysfunction and Alzheimer's disease (AD) remains a current topic of interest. Previous research has primarily concentrated on examining the impact of thyroid dysfunction on the risk of developing AD, or solely explored the mechanisms of interaction between hypothyroidism and AD, a comprehensive analysis of the mechanisms linking thyroid dysfunction, including hyperthyroidism and hypothyroidism, to Alzheimer's disease (AD) still require further elucidation. Therefore, the aim of this review is to offer a thorough and comprehensive explanation of the potential mechanisms underlying the causal relationship between thyroid dysfunction and AD, highlighting the existence of a vicious circle. The effect of thyroid dysfunction on AD includes neuron death, impaired synaptic plasticity and memory, misfolded protein deposition, oxidative stress, and diffuse and global neurochemical disturbances. Conversely, AD can also contribute to thyroid dysfunction by affecting the stress repair response and disrupting pathways involved in thyroid hormone (TH) production, transport, and activation. Furthermore, this review briefly discusses the role and significance of utilizing the thyroid as a therapeutic target for cognitive recovery in AD. By exploring potential mechanisms and therapeutic avenues, this research contributes to our understanding and management of this devastating neurodegenerative disease.